2010
DOI: 10.1088/0953-8984/22/29/295504
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence properties of undoped LiBaAlF6single crystals

Abstract: This paper presents the results of the study of electronic excitations in undoped LiBaAlF(6) single crystals by means of luminescence spectroscopy and complimentary optical methods. The intrinsic emission at 4.2 eV due to self-trapped excitons was identified. The fast nanosecond defect-related luminescence was revealed at 3.0 eV. Both emissions degrade under electron beam irradiation, the most probable reason of which is defect creation introducing an additional non-radiative relaxation channel prohibiting ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 26 publications
8
22
0
Order By: Relevance
“…From [5] it follows that LBAF single crystal at 10 K has E g = 12.3 eV. This value is fairly consistent with the early reported estimation of E g = 12.1 eV [3]. Crystallographic data for the real LBAF crystals were presented in [6].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…From [5] it follows that LBAF single crystal at 10 K has E g = 12.3 eV. This value is fairly consistent with the early reported estimation of E g = 12.1 eV [3]. Crystallographic data for the real LBAF crystals were presented in [6].…”
Section: Introductionsupporting
confidence: 85%
“…We are aware of only a few research works on this host. Luminescent properties and self-trapped excitons in undoped LBAF crystals have been studied in [3]. From the luminescence optical spectroscopy data it follows that the experimental estimation of the LBAF energy bandgap is E g % 12.1 eV [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is homologous to the above-mentioned LiAEAlF 6 group but has a different, more complex structure described by Merkulov et al (2008). The luminescence properties of undoped LiBAF single crystals have been studied by us (Omelkov et al, 2010). Wet chemical synthesis and luminescent properties of Ce-and Eudoped LiBAF (Belsare et al, 2009a, b) have been briefly reported.…”
Section: Introductionmentioning
confidence: 99%
“…This applies not only to study of the crystal structure [9], but also to study of the luminescence and optical properties of both the undoped crystals [10][11][12], and crystals doped with Ce 3+ [13,14], Cr 3+ [15], and Pr 3+ [16]. Electronic properties of undoped Li M AlF 6 crystals have been studied experimentally using vacuum ultraviolet optical and luminescence spectroscopy [12,17], and X-ray photoelectron spectroscopy techniques [17].…”
Section: Introductionmentioning
confidence: 99%